Предмет: Алгебра, автор: 12assua12

40 баллов даю
А73- только

Приложения:

Ответы

Автор ответа: zinaidazina
0

                                  f(x)=\frac{x^{2}+5 x}{x-2}

1)  f'(x)=(\frac{x^{2}+5 x}{x-2} )'=\frac{(x^{2}+5 x)'*(x-2)-(x^{2} +5x)*(x-2)'}{(x-2)^2}=

    =\frac{(2x+5)*(x-2)-(x^{2} +5x)*1}{(x-2)^2}=\frac{2x^2+5x-4x-10-x^{2} -5x}{(x-2)^2}=

    =\frac{x^2-4x-10}{(x-2)^2}

                            f'(x)=\frac{x^2-4x-10}{(x-2)^2}

2)  f'(3)=\frac{3^2-4*3-10}{(3-2)^2}=\frac{9-12-10}{1^2}=-13

                           f'(3)=-13

3)       f'(x)*(x-2)=f'(3)

\frac{x^2-4x-10}{(x-2)^2}*(x-2)=-13

\frac{x^2-4x-10}{x-2}=-13

\frac{x^2-4x-10}{x-2}+13=0

\frac{x^2-4x-10+13*(x-2)}{x-2}=0

\frac{x^2-4x-10+13x-26}{x-2}=0

\frac{x^2+9x-36}{x-2}=0    

            ОДЗ:  x\neq 2

x^2+9x-36=0

D=81-4*1*(-36)=81+144=225=15^{2}

x_1=\frac{-9-15}{2}=-12

                x_1=-12

x_2=\frac{-9+15}{2}=3

                x_2=3  

Больший корень уравнения 3.

Ответ: 3

Похожие вопросы
Предмет: Русский язык, автор: Новичок7262